Radiocarbon dating, chronologic framework, and changes in accumulation rates of Holocene estuarine sediments from Chesapeake Bay - Colman, S. M.; Baucom, P. C.; Bratton, J. F.; Cronin, T. M.; McGeehin, J. P.; Willard, D.; Zimmerman, A. R.; Vogt, P. R. (Quaternary Research, 2002)
Rapidly accumulating Holocene sediments in estuaries commonly are difficult to sample and date. In Chesapeake Bay, we obtained sediment cores as much as 20 m in length and used numerous radiocarbon ages measured by accelerator mass spectrometry methods to provide the first detailed chronologies of Holocene sediment accumulation in the bay. Carbon in these sediments is a complex mixture of materials from a variety of sources. Analyses of different components of the sediments show that total organic carbon ages are largely unreliable, because much of the carbon (including coal) has been transported to the bay from upstream sources and is older than sediments in which it was deposited. Mollusk shells (clams, oysters) and foraminifera appear to give reliable results, although reworking and burrowing are potential problems. Analyses of museum specimens collected alive before atmospheric nuclear testing suggest that the standard reservoir correction for marine samples is appropriate for middle to lower Chesapeake Bay. The biogenic carbonate radiocarbon ages are compatible with (210)Pb and (137)Cs data and pollen stratigraphy from the same sites.Post-settlement changes in sediment transport and accumulation is an important environmental issue in many estuaries, including the Chesapeake. Our data show that large variations in sediment mass accumulation rates occur among sites. At shallow water sites, local factors seem to control changes in accumulation rates with time. Our two relatively deep-water sites in the axial channel of the bay have different long-term average accumulation rates, but the history of sediment accumulation at these sites appears to reflect overall conditions in the bay. Mass accumulation rates at the two deep-water sites rapidly increased by about fourfold coincident with widespread land clearance for agriculture in the Chesapeake watershed.
517wpTimes Cited:57Cited References Count:33

Radiocarbon dating of Marion-Dufresne cores MD99-2204, 2207, and 2209, Chesapeake Bay - Colman, S. M.; Bratton, J. F.; Baucom, P. C. (Initial Report on IMAGES V Cruise of the Marion-Dufresne to the Chesapeake Bay June 20-22, 1999, 2000)
id: 1414

Climate and lake-level history of the northern Altiplano Bolivia, as recorded in Holocene sediments of the Rio Desaguadero - Baucom, P. C.; Rigsby, C. A. (Journal of Sedimentary Research, 1999)
Strata exposed in terraces and modern cutbanks along the Rio Desaguadero contain a variety of lithofacies that were deposited in four distinct facies associations. These facies associations document a history of aggradation and downcutting that is Linked to Holocene climate change on the Altiplano.Braided stream, meandering stream, deltaic and shoreline, and la custrine sediments preserved in multi-level terraces in the northern Rio Desaguadero valley record two high-water intervals: one between 4500 and 3900 yr BP and another between 2000 and 2200 yr BP. These wet periods were interrupted by three periods of fluvial downcutting, centered at approximately 4000 yr BP, 3600 Sr BP, and after 2000 yr BP. Braided-river sediments preserved in a single terrace level in the southern Rio Desaguadero valley record a history of nearly continuous fluvial sedimentation from at least 7000 yr BP until approximately 3200 yr BP that was followed by a single episode (post-3210 ST BP) of down cutting and lateral migration.The deposition and subsequent fluvial downcutting of the northern strata was controlled by changes in effective moisture that can he correlated to Holocene water level fluctuations of Lake Titicaca, The deposition and dissection of braided-stream sediments to the south are more likely controlled by a combination of base-level change and sediment input from the Rio Mauri.
A197atTimes Cited:30Cited References Count:61